Evaluación De La Efectividad Del Portal Web En La Comunicación Y Participación Ciudadana De La Empresa Pública Municipal De Agua Potable Y Alcantarillado Del Cantón Quevedo, 2024. - Cedeño Sisalima, Kendry Dariana (2025)
The research “Evaluation of the effectiveness of the website in communication and citizen participation of the Empresa Pública Municipal de Agua Potable y Alcantarillado del cantón Quevedo (EPMAPAQ), 2024” addresses one of the major current challenges in public management: the digital transformation of government services. The study explores how the EPMAPAQ website can enhance interaction with citizens, fostering active participation in service management. The focus of this work is on analyzing the website’s use as a key tool to promote transparency and citizen trust. By rigorously examining interactive tools, the frequency of information updates, and accessibility, the research aims to understand how these variables influence user experience and their willingness to actively participate. The methodology includes structured surveys and in-depth interviews with key actors, enabling the collection of both quantitative and qualitative data. This mixed approach ensures a comprehensive view of the portal’s impact on citizens' daily lives. The study not only identifies deficiencies in the portal’s structure and functionality but also proposes practical solutions, such as a redesign of the website to optimize its accessibility and ease of use. In the end, the portal is expected to become not only more intuitive but also an effective platform for strengthening citizen participation and improving water service management.